1997
DOI: 10.1002/cber.19971300116
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interconversions in the System TP*Zn/CO2/Alcohol [Tp* = Substituted Tris(pyrazolyl)borate]

Abstract: The zinc hydroxide complexes Tp*Zn-OH with TpCUmjMe = tris(3-cumenyl-5-methylpyrazolyl)borate and TptBurMe = tris(3-tert-butyl-5-methylpyrazolyl)borate can be converted to the alkyl carbonate complexes Tp*Zn-OCOOR by reaction with dialkyl dicarbonates or with alcohol and COz. An alternative formation reaction is the treatment of the pyrazolyl borate with zinc perchlorate and potassium carbonate in alcohol. The interconversion between TpcUmrMeZn-OH and TpCUmrMeZn-OCOOMe in methanol-containing solution can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…We have previously described reactions of Tp*ZnϪOH complexes with CO 2 in alcohols, [7,8] with CS 2 in alcohols [7] and in nonprotic solvents, [12] and with phenylisothiocyanate. [7] We had two reasons to repeat such reactions with Tp Ph,Me ZnϪOH (2).…”
Section: Eactions Of Tp Phme Zn؊ohmentioning
confidence: 99%
“…We have previously described reactions of Tp*ZnϪOH complexes with CO 2 in alcohols, [7,8] with CS 2 in alcohols [7] and in nonprotic solvents, [12] and with phenylisothiocyanate. [7] We had two reasons to repeat such reactions with Tp Ph,Me ZnϪOH (2).…”
Section: Eactions Of Tp Phme Zn؊ohmentioning
confidence: 99%
“…Step (3): formation of weak associated precursor complex with CO 2 The second step in the first pathway is the formation of a weakly associated precursor complex (PC) from the reactants at infinite separation. The CO 2 molecule locates on the mirror plane perpendicular to the Zn-OH plane, as depicted in Fig.…”
Section: Step (1and2): Attack Of An H 2 O Molecule On One Of the Zn Ionmentioning
confidence: 99%
“…Previous work has shown that, in the presence of appropriate ligand environments and electron-rich metal centres, the reduction of CO 2 is possible, producing carbonates, oxalates, for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A variety of transition metal complexes with M-OR fragments undergo insertion reactions with CO 2 [4,6,7,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own attempts to make these reactions catalytic have met with little success so far. [52] Although solvent mixtures containing water (e.g., dichloromethane/methanol/water 6:4:1) can be found that will dissolve the complexes [Tp 'ZnÀOH] and that allow the determination of the pK a values of the corresponding Tp'ZnÀOH 2 complexes, [53] water could not yet be made a reagent in their chemistry. The advantage of the encapsulation by Tp' ligands that makes the existence of the Zn À OH function at neutral pH possible is a disadvantage in terms of the formation of charged species (i.e., cationic [Tp'ZnL] complexes or intermediates for proton transfers), and also the neutral [TpZnÀX] complexes (e.g., phosphates or carboxylates) with their hydrophobic exterior are too stable and too inert as to favor catalytic turnover.…”
Section: Organophosphate Cleavagesmentioning
confidence: 99%